2019
DOI: 10.33425/2641-4317.1008
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lithium Carbonate in Concept of Double Mood Stabilizer for Treatment of Bipolar Mania

Abstract: Background: To systematically evaluate the difference in efficacy of valproate and valproate combination with lithium carbonate for therapy of bipolar mania in China. And to provide evidences for double mood stabilizer in therapy of bipolar disorder. Methods: A meta-analysis was performed of all the literatures germane to estimate the bipolar mania patients treated with valproate combination with lithium and only valproate randomized controlled trials (RCTs) from 2007 to 2014. Odds ratios (ORs) and 95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The concept of double mood stabilizer have been suggested for treatment bipolar disorder [11,12,13].The clinical therapeutic effect is more than that only one mood stabilizer for patients with bipolar disorder with less interaction between drugs.But this is combination of lithium and valproate,which was more common than that of lithium and lamortigine.However,lamotrigine is called "mood stabilizer for depression" and also can decrease the switch to mania induced by antidepressant [8,14],which may further strengthen the mood stability of lithium to for improve depression symptom that were less likely to respond to the treatment of single lithium or divalproex.And the study also shown that lamotrigine is superior to placebo in treatment of rapid cycling bipolar disorder [15]. Case report addition of lamotrigine to valproic acid had a successful outcome in a case of rapid-cycling bipolar affective disorder [16].So their combination may play a role on bipolar disorder,especially on rapid cycling bipolar disorder.This study was that meta-analysis about lamotrigine combing with lithium was sued for treatment of rapid cycling bipolar disorder.…”
mentioning
confidence: 99%
“…The concept of double mood stabilizer have been suggested for treatment bipolar disorder [11,12,13].The clinical therapeutic effect is more than that only one mood stabilizer for patients with bipolar disorder with less interaction between drugs.But this is combination of lithium and valproate,which was more common than that of lithium and lamortigine.However,lamotrigine is called "mood stabilizer for depression" and also can decrease the switch to mania induced by antidepressant [8,14],which may further strengthen the mood stability of lithium to for improve depression symptom that were less likely to respond to the treatment of single lithium or divalproex.And the study also shown that lamotrigine is superior to placebo in treatment of rapid cycling bipolar disorder [15]. Case report addition of lamotrigine to valproic acid had a successful outcome in a case of rapid-cycling bipolar affective disorder [16].So their combination may play a role on bipolar disorder,especially on rapid cycling bipolar disorder.This study was that meta-analysis about lamotrigine combing with lithium was sued for treatment of rapid cycling bipolar disorder.…”
mentioning
confidence: 99%